2021
DOI: 10.35772/ghm.2020.01096
|View full text |Cite
|
Sign up to set email alerts
|

The primary tumor location in colorectal cancer: A focused review on its impact on surgical management

Abstract: The primary tumor location (PTL) has attracted increasing attention in recent years for colorectal cancer (CRC) patients. Although the underlying mechanisms for differences caused by PTL remain still unclear, right-sided colon (RCC) and left-sided colon (LCC) are now considered as distinct entities because of their different molecular profile and clinical response to surgery and chemotherapy. In this article, we review the influence of PTL particularly on surgical management of primary and metastatic CRC setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Several clinical studies have demonstrated that left- and right-sided colon tumors are different diseases, based also on their surgical procedures, as well as complication rates and recurrence patterns [ 50 ]. In particular, right-sided colon cancers are characterized by high immunogenicity and a worse prognosis [ 3 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated that left- and right-sided colon tumors are different diseases, based also on their surgical procedures, as well as complication rates and recurrence patterns [ 50 ]. In particular, right-sided colon cancers are characterized by high immunogenicity and a worse prognosis [ 3 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRC is a highly heterogeneous group of tumors, and the pathogenesis of CRC is a complex and multifactorial process involving the accumulation of various genetic and epigenetic alterations [ 5 ]. Beyond these alterations, it is widely accepted that tumor location (right- and left-sided colon cancer, rectal cancer) is a crucial factor involved in disease progression as well as prognosis and influences disease management [ 6 , 7 , 8 ]. Right-sided colon cancer (RSCC) occurs within the cecum, ascending colon, hepatic flexure and transverse colon, while left-sided colon cancer (LSCC) arises in the splenic flexure, descending colon and sigmoid colon.…”
Section: Introductionmentioning
confidence: 99%
“…The contributors include more mutations of the C-K-RAS proto-oncogene, mucinous type of tumor, older age, female sex and comorbidities [ 10 ], which may result in R-CC being more likely to relapse after surgery. R-CC patients may have a better prognosis after curative resection in TNM stage I-II and a worse survival after recurrence in TNM stage III [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%